(untitled) (Eurasian Research Bulletin, 2023)
А result of scientific researches , the revolution of science and technology, which was achieved at the beginning of our century , led to unprecedented achievements in the health care system . Development of anesthesiology and resuscitation, improvement of pre-operative preparation and post-operative intensive therapy, repair of surgery, especially diagnostic service with modern technical equipment, quality, radical, expanded operations , even available to the patient at the same time It made it possible to eliminate several pathologies (simultaneous operations) (Akbarov M.M. 2016; Feng. 2017).